Energy Saving and Renewable Energy production at University of Kashan, Kashan, Iran - Monemzadeh, Majid; Talebi-Dastenaei2, Mahnaz (Journal of Sustainability Perspectives, 2021)
University of Kashan was founded in 1974 and is the oldest institution of higher education in Kashan. Kashan (33° 58' 59" N / 51° 25' 56" E) climate is classified as a hot and dry by the Köppen-Geiger system. This climate causes a large amount of energy consumption for University at springs and summers. On the other hand, it means that sun is shining strongly for more than 6 months and University of Kashan has been working on some solutions to use solar energy and decrease dependency on the old fossil-fuel energy system. The current paper studies some of the main activities of University of Kashan on Energy Saving and Renewable Energy Production programs such as CCHP plant (The first Combined Cool, Heat, and Power plant in Iran), using solar panels and energy-efficient appliances.